A Systematic Review of Non‐Echo Planar Diffusion‐Weighted Magnetic Resonance Imaging for Detection of Primary and Postoperative Cholesteatoma. (2nd November 2015) - van Egmond, Sylvia L.; Stegeman, Inge; Grolman, Wilko; Aarts, Mark C. J.
Abstract : Objective: To investigate the diagnostic value of non–echo planar diffusion‐weighted magnetic resonance imaging (DW‐MRI) for primary and recurrent/residual (postoperative) cholesteatoma in adults (≥18 years) after canal wall up surgery. Data Sources: We conducted a systematic search in PubMed, Embase, and Cochrane up to October 22, 2014. Review methods: All studies investigating non–echo planar DW‐MRI for primary and postoperative cholesteatoma were selected and critically appraised for relevance and validity. Results: In total, 779 unique articles were identified, of which 23 articles were included for critical appraisal. Seven articles met our criteria for relevance and validity for postoperative cholesteatoma. Four studies were additionally included for subgroup analysis of primary cases only. Ranges of sensitivity, specificity, positive predictive value, and negative predictive value yielded 43%‐92%, 58%‐100%, 50%‐100% and 64%‐100%, respectively. Results for primary subgroup analysis were 83%‐100%, 50%‐100%, 85%‐100%, and 50%‐100%, respectively. Results for subgroup analysis for only postoperative cases yielded 80%‐82%, 90%‐100%, 96%‐100%, 64%‐85%, respectively. Despite a higher prevalence of cholesteatoma in the primary cases, there was no clinical difference in added value of DW‐MRI between primary and postoperative cases. Conclusion: We found a high predictive value of non–echo planar DW‐MRI for the detection of primary and postoperative cholesteatoma. Given the moderate quality of evidence, we strongly recommend both the use of non‐echo planar DW‐MRI scans for the follow‐up after cholesteatoma surgery, and when the correct diagnosis is questioned in primary preoperative cases.